2021
DOI: 10.3390/jcm11010004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Bile Acid Metabolism to Improve Plasma Lipid and Lipoprotein Profiles

Abstract: New drugs targeting bile acid metabolism are currently being evaluated in clinical studies for their potential to treat cholestatic liver diseases, non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH). Changes in bile acid metabolism, however, translate into an alteration of plasma cholesterol and triglyceride concentrations, which may also affect cardiovascular outcomes in such patients. This review attempts to gain insight into this matter and improve our understanding of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 159 publications
(200 reference statements)
0
16
0
Order By: Relevance
“…BAS mainly lowers LDL cholesterol between 15% and 30% and slightly increases serum HDL concentrations by 3–5% [ 28 ]. However, their effect on serum triglyceride concentrations remains controversial [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…BAS mainly lowers LDL cholesterol between 15% and 30% and slightly increases serum HDL concentrations by 3–5% [ 28 ]. However, their effect on serum triglyceride concentrations remains controversial [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the classical pathway of BA synthesis accounts for at least 75% of total BA production and is considered to be the main pathway of BA biosynthesis (10). Primary BAs are amino-conjugated at the carboxyl group, with a ratio of glycine to taurine conjugates of approximately 3:1 (11). BAs may also bind to sulfate or glucuronic acid to form fully ionized, negatively charged hydrophilic polar molecules, and these bound forms of BAs subsequently discharge into the intestine with bile.…”
Section: Basmentioning
confidence: 99%
“…BAs have a variety of physiological roles, the most important of which is to promote the digestion and absorption of lipids (11). BA molecules have hydrophilic and hydrophobic sides in their configuration, which endows them with strong interfacial activity to reduce the surface tension between oil and water phases and promote lipid emulsification.…”
Section: Functions Of Bamentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported byZhou et al, (2018), who published the significant rise in CVDs patients, whereasLiu et al, (2015) reported no significant difference between both groups.The results of the present study indicated that high level of triglyceride was found in the serum of patients and significantly more than in control < (p = 0.0001) , Results by Talayero & Sacks,(2011) andAberra et al, (2020) reached to the same conclusion, but Sun,(2021) found no significant difference in the level of TG between CVDs patients and healthy individuals. Although cholesterol plays a fundamental role in a plethora of intracellular mechanisms, it is known that individuals with highplasma cholesterol concentration are at increased risk of atherosclerotic heart disease(Zhang et al,2021) . We found significant increase in blood cholesterol of CVDs patients compared to its level in control (p = 0.0001).…”
mentioning
confidence: 99%